Patient/Caregiver and Expert Stakeholder Perspectives on High‐Quality Palliative Care for Patients with Advanced Cancer. (15th September 2021) - O'Hanlon, Claire; Giannitrapani, Karleen; Gamboa, Raziel; Walling, Anne; Lindvall, Charlotta; Garrido, Melissa; Asch, Steven; Canning, Mark; Lorenz, Karl
Abstract : Research Objective: To inform priorities for palliative care quality monitoring using natural language processing applied to clinical notes in electronic health records, we aimed to describe expert stakeholder and patient/caregiver conceptualizations of high‐quality palliative care for patients receiving care for advanced cancer. Study Design: We conducted two modified RAND‐UCLA appropriateness panels to prioritize palliative care process quality measures relevant to patients with advanced cancer from the perspective of cancer patients/caregivers and cancer palliative care expert health system stakeholders. We identified 64 candidate quality measures via a measure scan. Next, expert panelists discussed and prioritized quality measures. To facilitate ease of comprehension, we had patients/caregivers discuss, evaluate, and prioritize a sub‐set of 21 quality measures highly rated by the expert panel. Panel discussions (8 hours each) were recorded, transcribed, and independently double‐coded in Atlas.ti using an a priori framework for palliative symptom care: 1) experience of illness/symptoms, 2) screening/assessment/diagnosis 3) management/plan/treatment, 4) iterative management (follow‐up), and 5) documentation, as well as one emergent theme: 6) equity. Quotations were examined separately within each code and themes were generated through team discussion until consensus was reached. Population Studied: The panels were composed of ten palliative care expert stakeholders: 7 physicians, 2 nurses, 1 social worker) and nine patients/caregivers with cancer experience. Principal Findings: Patients/caregivers and expert stakeholders contributed different perspectives of what high quality symptom care means for advanced cancer patients. Patients/caregivers emphasized the need for comprehensive and proactive screening and assessment, especially for pain and mental health symptoms, due to reluctance to being perceived as "weak" and beliefs that there is "not a heck of a lot [clinicians] can do" to address their symptoms. Patients/caregivers valued continuity and communication among their many clinical care providers as well as acknowledgment or discussion of the written information they provided (e.g., on a symptom screening form). Expert stakeholders emphasized the need for symptom screening to be tied to management plans, rather than measuring them separately, as well as the need to treat symptoms to patient satisfaction rather than an "artificial number." Expert stakeholders expressed uncertainty about the best way to ask about or acknowledge symptoms, like fatigue, that have few management options. Patients/caregivers and expert stakeholders agreed on the need to prioritize "iterative" management to monitor the efficacy of treatment plans and the need to monitor differences in care quality provided to medically underserved and minority populations. Conclusions: Patients contribute a unique perspective to quality measure prioritization, which is typically the domain of clinicians and administrators. Patients and caregivers took a "systems view" of quality, based on their experiences interacting with clinicians inside and outside VA. Expert stakeholders, in contrast, took a "one on one" view of quality, emphasizing measurability of the aspects of care under the control of a single clinician. Incorporating the perspective of patients/caregivers highlighted the importance of proactive symptom screening for providing high quality palliative care for patients with advanced cancer. Implications for Policy or Practice: Future efforts to automate quality monitoring should find ways to incorporate and operationalize patient conceptualizations of healthcare quality. Primary Funding Source: Department of Veterans Affairs.